EYA1 and SIX1 drive the neuronal developmental program in cooperation with the SWI/SNF chromatin-remodeling complex and SOX2 in the mammalian inner ear - Ahmed, Mohi; Xu, Jinshu; Xu, Pin-Xian (Development (Cambridge), 2012)
Inner ear neurogenesis depends upon the function of the proneural basic helix-loop-helix (bHLH) transcription factors NEUROG1 and NEUROD1. However, the transcriptional regulation of these factors is unknown. Here, using loss- and gain-of-function models, we show that EYA1 and SIX1 are crucial otic neuronal determination factors upstream of NEUROG1 and NEUROD1. Overexpression of both Eya1 and Six1 is sufficient to convert non-neuronal epithelial cells within the otocyst and cochlea as well as the 3T3 fibroblast cells into neurons. Strikingly, all the ectopic neurons express not only Neurog1 and Neurod1 but also mature neuronal markers such as neurofilament, indicating that Eya1 and Six1 function upstream of, and in the same pathway as, Neurog1 and Neurod1 to not only induce neuronal fate but also regulate their differentiation. We demonstrate that EYA1 and SIX1 interact directly with the SWI/SNF chromatin-remodeling subunits BRG1 and BAF170 to drive neurogenesis cooperatively in 3T3 cells and cochlear nonsensory epithelial cells, and that SOX2 cooperates with these factors to mediate neuronal differentiation. Importantly, we show that the ATPase BRG1 activity is required for not only EYA1- and SIX1-induced ectopic neurogenesis but also normal neurogenesis in the otocyst. These findings indicate that EYA1 and SIX1 are key transcription factors in initiating the neuronal developmental program, probably by recruiting and interacting with the SWI/SNF chromatin-remodeling complex to specifically mediate Neurog1 and Neurod1 transcription.